2016
DOI: 10.1097/ypg.0000000000000111
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of SNPs from the FADS1-FADS2 gene cluster with major depression or suicidal behavior

Abstract: Fatty acid desaturase genes (FADS1-FADS2) encode for desaturases participating in biosynthesis of long-chain polyunsaturated fatty acids (LC-PUFAs). Since LC-PUFAs are implicated in major depressive disorder (MDD) and suicide risk, and both are partly heritable, we studied the association of FADS1-FADS2 polymorphisms with MDD (635 cases, 480 controls), and suicide attempt status (291 attempters, 338 non-attempters).. Eighteen FADS-related single-nucleotide polymorphisms (SNPs) were genotyped from Caucasians en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…This fatty acid signature would suggest that EPA+DHA deficits cannot be attributed to impaired microsomal desaturase and elongase activity. This is also supported by a recent genotyping study which did not observe an association between common single-nucleotide polymorphisms in FADS1 or FASD2 genes and depression or suicidality in MDD patients [127]. However, DNA methylation in the Elovl5 gene was found to be associated with depression and suicidality [128], and abnormalities in FADS1 and FADS2 mRNA expression have been observed in the postmortem prefrontal cortex of patients with mood disorders [129131].…”
Section: Etiological Mechanismsmentioning
confidence: 54%
“…This fatty acid signature would suggest that EPA+DHA deficits cannot be attributed to impaired microsomal desaturase and elongase activity. This is also supported by a recent genotyping study which did not observe an association between common single-nucleotide polymorphisms in FADS1 or FASD2 genes and depression or suicidality in MDD patients [127]. However, DNA methylation in the Elovl5 gene was found to be associated with depression and suicidality [128], and abnormalities in FADS1 and FADS2 mRNA expression have been observed in the postmortem prefrontal cortex of patients with mood disorders [129131].…”
Section: Etiological Mechanismsmentioning
confidence: 54%
“…However, the link between FADS haplotype and the risk of developing neuropsychiatric disorders (schizophrenia or depression) is weak ( Fallin et al, 2004 ; Schizophrenia Psychiatric Genome-Wide Association Study (GWAS) Consortium, 2011 ). A study conducted in patients with major depression found no association between FADS single nucleotide polymorphisms and major depression ( Sublette et al, 2016 ). Recently, a study suggested that genetic variation in the FADS gene influences the ω6/ω3 PUFAs ratio which appears to be associated with major depression ( Cribb et al, 2017 ).…”
Section: The Role Of ω3 Pufas In Depression and Anxiety Disordersmentioning
confidence: 99%
“…Previous research has explored the role of the FADS gene cluster in schizophrenia [ 33 ], response to omega-3 supplementation [ 39 ] and infant cognition [ 40 ]. Studies investigating the FADS genotype in MDD have been inconclusive, though sample sizes have been comparatively small [ 41 , 42 ]. On the one hand, this adds weight to the biological plausibility of causal inference, being involved in a rate-limiting step in the elongation of short-chain fatty acids to the long-chain derivatives important for brain health (such as EPA and DHA).…”
Section: Discussionmentioning
confidence: 99%